DETERMINING THE COST OF CLEAN MUSHROOM BAGLOG PRODUCTS WITH COSTING PROCESS METHOD: (Study on Mas Kantak Oyster Mushroom Cultivation UKM) - Niken Suryaningtyas; Diana Elvianita Martanti (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2018)
Calculation of cost of production by using the Process Costing method is the calculation of costs for certain products that are produced from month to month are the same. The purpose of this study is to evaluate the calculation of cost of production from 2015 to 2017 in the business of Oyster Mushroom owned by Mas Kantak. This research uses descriptive quantitative method so that it can find out the calculation of the cost of production from the process of making baglog of oyster mushrooms. The results obtained from this study are that production costs increase every year, so the production costs in 2015 were Rp 5,648,800 with a perunit price of Rp 1,412, in 2016 amounting to Rp 4,741,707 with a perunit price of Rp 1,435, whereas in the year 2017 production costs amounting to Rp 5,941,403 with a perunit price of Rp 1,485.